The criminality of juveniles through the prism of criminologically significant manifestations of extremism - E.V. Demidova-Petrova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
The paper considers youth extremism as a self-deterministic phenomenon, which includes the processes of transformation of the criminality of juveniles into the criminal activity of young people. Special attention has been paid to the fact that youth extremism develops in the criminological problems experienced by juveniles and manifested in their adulthood. It has been noted that the economic difficulties aggravate the crisis of values and norms of legitimate behavior, thereby creating a favorable environment for the emergence, development, and spread of extremism among young people. The relation between criminality in juveniles and extremism lies in the “rejuvenation” of the latter. Thus, it has been revealed that most extremist crimes are committed by persons aged 13–18 years. The main tool that favors the involvement of juveniles in both general criminal and extremist activities is the Internet, which serves as a technology and means of transforming juvenile criminality into concrete criminal manifestations.